Evaluation of the thermal treatment effect on the entrapment of the powder in internal channels of PBF-LB parts - Teixeira, Óscar Francisco Reis Mota (2021)
Additive manufacturing (AM) can be seen as a disruptive process that builds complex components layer upon layer. Two of its distinct technologies are Selective Laser Melting (SLM) and Electron Beam Melting (EBM), which are powder bed fusion processes that create metallic parts with the aid of a beam source. Two of the most studied and manufactured superalloys in metal AM are the Inconel 718 (IN718) and the Ti-6Al-4V. The former is commonly employed in the marine, nuclear power plants, gas turbines, and aerospace field due to its capacity of retaining good mechanical properties at high temperatures, while the latter is often used in the aerospace field due to its low density and high melting point, and in the biomedical area owing to its high corrosion resistance and excellent biocompatibility when in contact with tissues or bones of the human body. Nevertheless, the aforementioned alloys frequently require a post-processing heat treatment in order to enhance certain mechanical properties, modify the microstructure and reduce the residual stresses (RS), which are induced by thermal principles, as the gradient temperature is high because of the heating and thermal expansion upon the deposition of a new layer, and its subsequent cooling. Therefore, production errors in the components might occur due to geometrical distortion. Thus, it is mandatory to understand the expected orientation and magnitude of the RS in order to do accurate predictions of the final part properties. The initial goal of this dissertation was to evaluate the thermal treatment effect on the entrapment of IN718 powder in internal channels of laser beam powder beam fusion manufactured components. However, due to the current pandemic, Polito’s laboratories could only be used by researchers and PhD students. Having that constraint, I was advised, by Professor Francisco Silva, to write two review papers that would replace the experimental work of this thesis, being the first about residual stresses and heat treatments of Selective Laser Melted IN718 parts and the second about residual stresses and heat treatments of Electron Beam Melted and Selective Laser Melted Ti-6Al-4V components. From the first scientific paper one can conclude that the expected microstructure in the as-built state of the IN718 components is characterized by fine columnar grains and a saturated γ matrix with the presence of the Laves phase and carbides. This heterogeneous microstructure promotes unfavourable anisotropic mechanical properties, meaning that, for high and cyclic loads applications, heat treatments must be conducted. In addition, it was also shown that RS can be lowered by applying heat treatments and favourable printing parameters, i.e. high scanning speed and low laser power. Finally, from the second review paper, it can be concluded that that the expected asbuilt microstructure of the Ti–6Al–4V alloy is different in both manufacturing processes, mainly due to the distinct cooling rates. However, heat treatments can modify the microstructure, reduce RS, and increase the ductility, fatigue life, and hardness of the components. Furthermore, distinct post-treatments can induce compressive RS on the part’s surface, consequently enhancing the fatigue life.